Clinical implication of platelet-lymphocyte ratio and PD-L1 in breast cancer patients - Lu, Qianyi; Qin, Tao; Xu, Fei; Zeng, Yinduo; Xia, Wen; Zheng, Qiufan; Lee, Kaping; Zhang, Kai; Qin, Ge; Kong, Man Tek; Hong, Ruoxi; Shi, Yanxia; et al. (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: The anti-tumor action of the host immune systems and cancer-immune interaction are associated with tumor prognosis. Combination of neutrophil-lymphocyte ratio (NLR)/platelet-lymphocyte ratio (PLR) and programmed death ligand-1 (PD-L1) in predicting prognosis in breast cancer has not been reported. The aim of this study is to evaluate the prognostic role of NLR/PLR and PD-L1 in breast cancer. Methods: A total of 870 patients with breast cancer treated in Sun Yat-sen University Cancer Center from 2000 to 2012 with known PD-L1 status were included. Clinicopathological data and pretreatment complete blood count (CBC) were retrospectively collected. Chi-square test and Mann-Whitney U test were used to compare baseline characteristics, Kaplan-Meier and univariate Cox proportional hazards model analyses were used to compare the survival of patients between different groups. Results: High PLR group achieved worse result than low PLR group in overall survival (OS) and disease-free survival (DFS) (5-year OS rate: 82.6% vs. 88.8%, P=0.010; 5-year DFS rate: 78.7% vs. 85.6%, P=0.003). High PLR was associated with shorter DFS [adjusted HR =1.525, 95% confidence interval (CI): 1.111–2.094, P=0.009] and OS (adjusted HR =1.527, 95% CI: 1.073–2.174, P=0.019). NLR was not associated with patients’ survival outcome. Patients with PD-L1 expression and high PLR had the worst prognosis. The 5-year DFS rates were 68.4%, and 85.8% in high PLR + PD-L1(+) group and low PLR + PD-L1(−) group respectively (P=0.002). The 5-year OS rates were 73.4% and 90.1%, respectively (P